Clinical Features and Prognosis of Cancer Patients Requiring Intensive Care Unit Admission: Clinical Features and Prognosis in ICU Cancer Patients - Sunil, Reena Kumari; Alvi, Atiqa; Baloch, Saba Ajaz; Khan, Tooba (Pakistan Journal of Health Sciences, 2026)
Cancer patients are at risk of admission to the critical care unit either due to primary illness or as a consequence of treatment. Objectives: To determine clinical features and cancer patients’ prognosis necessitating ICU (Intensive Care Unit) admission. Methods: This cross-sectional analytical study at the critical care unit of Ziauddin Medical University Hospital was done on cancer patients fulfilling eligibility criteria between July 2023 and December 2023. Along with demographics, Acute Physiology and Chronic Health Evaluation (APACHE) II score, Sequential Organ Failure Assessment (SOFA) score, and ECOG were reported. SPSS version 23.0 was used for data analysis. For comparing clinical characteristics and outcomes between different subgroups, the t-test and chi-square test were applied, keeping p<0.05 as statistically significant. Results: Patients having hematological malignancy had a significantly lengthier hospital stay before ICU admittance compared to those with solid tumors (p=0.01). Chemotherapy use was significantly more frequent (p<0.01), and sepsis/septic shock was a more common cause of ICU admission (p=0.05). On ICU admission, renal dysfunction (p<0.01), leukocyte count (p=0.04), thrombocyte count (p=0.05), and C-reactive protein levels (p<0.01) showed significant differences between the groups. During ICU stay, sepsis/septic shock remained significantly different between groups (p<0.01). Additionally, overall survival outcomes differed significantly, with higher survival observed in patients with solid tumors (p<0.01). Conclusion: The type of malignancy significantly influenced ICU outcomes, with hematological cancers associated with greater disease severity and poorer prognosis, while solid tumors showed better survival.